Contact resistivity of amorphous and crystalline GeCu2Te3 to W electrode for phase change random access memory. (1st June 2016) - Shindo, S.; Sutou, Y.; Koike, J.; Saito, Y.; Song, Y.-H.
Abstract: We have investigated the contact resistivity of GeCu2 Te3 (GCT) phase change material to a W electrode using the circular transfer length method (CTLM). The contact resistivity ρ c of as-deposited amorphous GCT to W was 3.9×10 −2  Ω cm 2 . The value of ρ c drastically decreased upon crystallization and crystalline GCT that annealed at 300 °C showed a ρ c of 4.8×10 −6  Ω cm 2 . The ρ c contrast between amorphous (as-deposited) and crystalline (annealed at 300 °C) states was larger in GCT than in conventional Ge2 Sb2 Te5 (GST). Consequently, it was suggested from a calculation based on a simple vertical structure memory cell model that a GCT memory cell shows a four times larger resistance contrast than a GST memory cell.